A new method to use Water Pinch Analysis for complex wastewater scenarios - Leo-Paul Vaurs; Chaowana Yirong (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
A new method was developed to easily determine process critical concentrations allowing the use of Water Pinch Analysis to minimize the fresh water (FW) requirement of processes dealing with complex wastewater. This method consists in experimentally recycling water within the studied process until some process units get their key performance indicators negatively impacted. This paper provides all the mathematical tools to calculate the critical concentrations of a generic compound called “contaminant X” based on the critical number of recyclings and effectively use Water Pinch Analysis. This developed method was applied to a continuous and mix batch/continuous process with or without storage tanks, and two scenarios where some processes could remove a fraction of “contaminant X”,  froma biological process for example (such as anaerobic digestion). The Near Neighbour Algorithm had to be slightly modified to be used in pure batch or mix batch/contiguous processes with without storage tank. In all cases, the FW requirement was minimized while guaranteeing that all processes were working at optimal performances.